Advances in monkeypox: exploring vaccines and therapeutic drugs for prevention and treatment - Maryam Ajel; Parisa Zeynali; Emad Behboudi (Journal of Zoonotic Diseases)
The most extensive monkeypox outbreak in history commenced in 2022 and has swiftly disseminated globally. This review aims to succinctly outline host immune reactions to orthopoxviruses, present an insight into available vaccines to counteract the epidemic, and delve into clinical research and animal studies examining induced immunity against monkeypox induced via the vaccinia virus-based monkeypox vaccines. It addresses current concerns about the outbreak and suggests optimal vaccine utilization as a control measure. During the 1980s, surveillance studies in Central Africa and subsequent outbreaks demonstrated that smallpox vaccines were approximately 85% effective against monkeypox. These findings are substantiated by numerous animal studies, primarily in primates, involving live virus challenges through different inoculation methods, consistently showcasing high levels of protection and immunity post-vaccination. Smallpox vaccines emerge as effective countermeasures for managing monkeypox outbreaks, although they do entail adverse effects, and second-generation, replicative vaccines have prohibited usage. Third-generation vaccines pose a challenge for rapid responses as they require 2 doses, which can be difficult for people with weak immunity. Insights from the COVID-19 outbreak must guide our collective approach to addressing the monkeypox outbreak and future outbreaks.